Web-Based Learning for Emergency Airway Management in Anesthesia Residency Training - Ada Hindle; Ji Cheng; Lehana Thabane; Anne Wong (Anesthesiology Research and Practice)
Introduction. Web-based learning (WBL) is increasingly used in medical education; however, residency training programs often lack guidance on its implementation. We describe how the use of feasibility studies can guide the use of WBL in anesthesia residency training. Methods. Two case-based WBL emergency airway management modules were developed for self-directed use by anesthesia residents. The feasibility of using this educational modality was assessed using a single cohort pretest/posttest design. Outcome measures included user recruitment and retention rate, perceptions of educational value, and knowledge improvement. The differences between pre- and postmodule test scores and survey Likert scores were analysed using the paired t test. Results. Recruitment and retention rates were 90% and 65%, respectively. User-friendliness of the modules was rated highly. There was a significant improvement in perceptions of the value of WBL in the postsurvey. There was a significant knowledge improvement of 29% in the postmodule test. Conclusions. Feasibility studies can help guide appropriate use of WBL in curricula. While our study supported the potential feasibility of emergency airway management modules for training, collaboration with other anesthesia residency programs may enable more efficient development, implementation, and evaluation of this resource-intensive modality in anesthesia education and practice.